Enhancing T cell responses and tumour immunity by vaccination with peptides conjugated to a weak NKT cell agonist. Issue 5 (18th January 2019) - Compton, Benjamin J.; Farrand, Kathryn J.; Tang, Ching-wen; Osmond, Taryn L.; Speir, Mary; Authier-Hall, Astrid; Wang, Jing; Ferguson, Peter M.; Chan, Susanna T. S.; Anderson, Regan J.; Cooney, Taylor R.; Hayman, Colin M.; et al.
Abstract : Through chemical synthesis we have designed out the toxicity associated with the powerful vaccine adjuvant α-GalCer. Abstract : Activated NKT cells can stimulate antigen-presenting cells leading to enhanced peptide antigen-specific immunity. However, administration of potent NKT cell agonists like α-galactosylceramide (α-GalCer) can be associated with release of high levels of cytokines, and in some situations, hepatotoxicity. Here we show that it is possible to provoke sufficient NKT cell activity to stimulate strong antigen-specific T cell responses without these unwanted effects. This was achieved by chemically conjugating antigenic peptides to α-galactosylphytosphingosine (α-GalPhs), an NKT cell agonist with very weak activity based on structural characterisation and biological assays. Conjugation improved delivery to antigen-presenting cells in vivo, while use of a cathepsin-sensitive linker to release the α-GalPhs and peptide within the same cell promoted strong T cell activation and therapeutic anti-tumour responses in mice. The conjugates activated human NKT cells and enhanced human T cell responses to a viral peptide in vitro . Accordingly, we have demonstrated a means to safely exploit the immunostimulatory properties of NKT cells to enhance T cell activation for virus- and tumour-specific immunity.